Highly Sensitive and Easily Recoverable Excitonic Piezochromic Fluorescent Materials for Haptic Sensors and Anti‐Counterfeiting Applications. (1st March 2020) - Man, Zhongwei; Lv, Zheng; Xu, Zhenzhen; Liao, Qing; Liu, Jiaxin; Liu, Yilang; Fu, Liyuan; Liu, Meihui; Bai, Shuming; Fu, Hongbing
Abstract: Piezochromic fluorescent (PCF) materials with distinct multicolor switching have attracted wide attention in many fields such as optoelectronic devices and deformation detection. However, few PCF materials with low‐pressure stimuli and good recoverability have been reported. A highly sensitive and easily recoverable PCF molecular system that can switch between green (G) and orange (O) emissions upon an extremely low piezoresponsive (PR) of 0.5 MPa and heating at 120 °C is demonstrated. A mechanistic study combining X‐ray diffraction analysis and the theoretical calculations reveal that a slight change in slipping‐angle of π‐stacks induced by mechanical pressure amplifies the exciton couplings from G to O J‐aggregates, leading to not only distinct PCF switching but also high emission efficiencies >0.5 owing to superradiance of J‐aggregate excitons. Benefiting from low MPa PR, high emission efficiency, and good recoverability applications including haptic sensors and anti‐counterfeiting application are demonstrated. This research introduces the effect of stimuli‐responsive excitonic coupling as new design guidance for developing PCF materials with low‐pressure stimuli, high emission efficiency, and good recoverability. Abstract : A high and efficient piezoresponsive multi‐color emission based on the aggregated states of a new conjugated D‐π‐A‐π‐D molecule TCAZCN is reported. The applications of the extraordinary excitonic PCF material, including haptic sensors and anti‐counterfeiting application, are demonstrated.